RECEPTION ANALYSIS OF MUSLIM AND NON-MUSLIM YOUTH IN BONDOWOSO REGENCY ON YOUTUBE CONTENT LOG IN - Siti Nur Fadilah; M. Khusna Amal; Hepni . (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
Da’wah activism is now widely manifested through social media. Social media is considered the most effective platform to reach a global audience, with YouTube being one of the primary platforms. Currently, YouTube is often utilized to disseminate radical da’wah messages. In this context, a da’i plays a crucial role in countering the spread of radical ideologies circulating on social media. With a relaxed preaching style, Habib Husein Ja’far al-Hadar promotes a friendly and moderate interpretation of Islam through his da’wah content, Log In. This content serves as a solution to bridging interfaith tensions in Indonesia. This study employs a qualitative descriptive approach with a case study method. The data analysis uses Stuart Hall's reception analysis framework. The results reveal that Muslim youth fully accept the digital da’wah messages of Habib Ja’far in Log In content, aligning with the intended meaning of the message creator. They are positioned in the Dominant Hegemonic reception category. In contrast, non-Muslim youth, particularly from the GPIB Immanuel Bondowoso Youth Movement (GP), occupy the Oppositional Position, entirely rejecting Habib Ja’far's da’wah messages in the Log In content. They interpret Log In as a platform aimed at promoting Islamization.